Ferumoxytol-enhanced magnetic resonance imaging methodology and normal values at 1.5 and 3T. Issue 1 (December 2016) - Stirrat, Colin; Alam, Shirjel; MacGillivray, Thomas; Gray, Calum; Forsythe, Rachael; Dweck, Marc; Payne, John; Prasad, Sanjay; Petrie, Mark; Gardner, Roy; Mirsadraee, Saeed; Henriksen, Peter; et al.
Abstract Background Ultrasmall superparamagnetic particles of iron oxide (USPIO)-enhanced magnetic resonance imaging (MRI) can detect tissue-resident macrophage activity and identify cellular inflammation. Clinical studies using this technique are now emerging. We aimed to report a range of normal R2* values at 1.5 and 3 T in the myocardium and other tissues following ferumoxytol administration, outline the methodology used and suggest solutions to commonly encountered analysis problems. Methods Twenty volunteers were recruited: 10 imaged each at 1.5 T and 3 T. T2* and late gadolinium enhanced (LGE) MRI was conducted at baseline with further T2* imaging conducted approximately 24 h after USPIO infusion (ferumoxytol, 4 mg/kg). Regions of interest were selected in the myocardium and compared to other tissues. Results Following administration, USPIO was detected by changes in R2* from baseline (1/T2*) at 24 h in myocardium, skeletal muscle, kidney, liver, spleen and blood at 1.5 T, and myocardium, kidney, liver, spleen, blood and bone at 3 T (p  < 0.05 for all). Myocardial changes in R2* due to USPIO were 26.5 ± 7.3 s-1 at 1.5 T, and 37.2 ± 9.6 s-1 at 3 T (p  < 0.0001 for both). Tissues showing greatest ferumoxytol enhancement were the reticuloendothelial system: the liver, spleen and bone marrow (216.3 ± 32.6 s-1, 336.3 ± 60.3 s-1, 69.9 ± 79.9 s-1;p  < 0.0001, p  < 0.0001, p  = ns respectively at 1.5 T, and 275.6 ± 69.9 s-1, 463.9 ± 136.7 s-1, 417.9 ± 370.3 s-1;p  < 0.0001, p  < 0.0001, p  < 0.01 respectively at 3 T). Conclusion Ferumoxytol-enhanced MRI is feasible at both 1.5 T and 3 T. Careful data selection and dose administration, along with refinements to echo-time acquisition, post-processing and analysis techniques are essential to ensure reliable and robust quantification of tissue enhancement. Trial registration ClinicalTrials.gov Identifier -NCT02319278 . Registered 03.12.2014.